G234(P) How children and young people self-manage their chronic illness: giving children a voice through photo-elicitation. (27th April 2015) - Carter, B; Dickinson, A; Ford, K; Bray, L; Water, T; Arnott, J
Abstract : Aim: To explore children's understanding and perception of their chronic illness and how this shapes their lives. Methods: A qualitative, participatory methodology that acknowledged the children's agency underpinned the study. We used photo-elicitation (photographs and interviews) to build knowledge grounded in the children's experiences. Forty-five children (6–12 years) from different diagnostic groups were recruited from hospital-based and support group settings in England, Tasmania and New Zealand. The children were given digital cameras and asked to record aspects of their lives and chronic illness. Children also had the option of including pre-existing photographs into the study. The researchers then undertook audio-recorded interviews that were guided by the photographs that the children wished to talk about. Most interviews were undertaken in the child's home. We undertook interpretative thematic analysis of the interviews and content analysis of the photographs. Results: Brokering was a key concept that underpinned the children's ways of accommodating the demands of chronic illness. The children focused on 'I can.......' rather than 'I can't.......' and were able to talk with confidence about certain aspects of self-management. The children used creative strategies to be 'like other children' and many were adept at negotiating risks and benefits in order to 'fit in'. Chronic illness – to a greater or lesser extent – was 'always there' but it was often successfully backgrounded through careful planning. The children actively foregrounded their achievements and focused on 'getting on' with being a child. This was not always easy. Whilst there was evidence of much resilience, this took effort and imagination from the children and their families. The children's parents/carers provided an important role in supporting the children's ability to self-manage their illness. Conclusion: Brokering and self-management were evident in the stories children told about themselves. The use of photo-elicitation gave the children control over those facets of their lives they wanted to discuss and share with the researchers. We found it a useful tool to discover those things that were important to the children and how they were active in ensuring that they could say 'I can.....'